Influence of Adipose Tissue-Derived Stem Cells on the Burn Wound Healing Process - Claudio Luciano Franck; Alexandra Cristina Senegaglia; Lidiane Maria Boldrini Leite; Sérgio Adriane Bezerra de Moura; Nathália Forti Francisco; Jurandir Marcondes Ribas Filho (Stem Cells International)
Burns are lesions in which the thermal energy of the causative agent transfers heat to the surface of the body, causing superficial or deep damage to the skin with protein denaturation in cells and biochemical maladjustments, which delay and disrupt the cicatricial process, increasing the chances of functional and aesthetic sequelae. This study evaluates the influence of adipose tissue-derived stem cells (ADSCs) on burn healing in terms of the size of the cicatricial space and quantified measures of collagen deposition, inflammatory infiltrate, blood vessels, and lymphatic vessels. Initially, intra-abdominal adipose tissue was resected from a single donor Wistar rat that was not part of any of the subsequent groups to obtain ADSCs by isolation and cell culture. Burns were made in the left lateral abdominal region of Wistar rats by contact with a square ceramic paper with a 484 mm2 area heated to 100°C for 30 seconds. Intradermal ADSC transplantation was performed in two stages. The first was on the same day of the burn, when 3.2×106 ADSCs were transplanted shortly after the burned region cooled, while the second stage occurred four days later with the same number of ADSCs. The progress was evaluated by immunohistochemical methods and H&E, Masson’s trichrome, Picrosirius red, and Lyve-1 immunofluorescence staining. Despite the quantitative similarity of blood vessels and the inflammatory infiltrate observed by H&E, there were statistically significant differences between the groups on the fourteenth day of evolution. The group that received ADSCs showed a reduction in the scar tissue area, increased collagen type III deposition, and a quantifiable reduction in lymphatic vessels, so we conclude that ADSCs influence the healing of total thickness burns in rats.